Hypothermic oxygenated perfusion in liver transplantation from expanded criteria donors - A. V. Shabunin; O. B. Loran; D. Yu. Pushkar; E. I. Veliev; M. G. Minina; P. A. Drozdov; S. A. Astapovich; E. A. Lidzhieva (Вестник трансплантологии и искусственных органов, 2024)
Objective: to improve the outcomes of liver transplantation (LTx) from expanded criteria donors (ECDs) through hypothermic oxygenated machine perfusion (HOPE).Material and methods. The study included 63 cases of LTx from suboptimal brain-dead donors. Group I (control) consisted of 34 persons in which liver transplant was preserved only by static cold storage (SCS), while group II (main) comprised 29 cases where ex situ HOPE was used after static preservation. We evaluated the efficacy and safety of the latter in a comparative clinical study and by studying ultrastructural changes in the liver using electron microscopy.Results. No statistically significant differences between the groups in terms of baseline characteristics of donors, recipients and several perioperative parameters (p > 0.05) were obtained. Peak aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels in the first week after transplantation were 1,052 (IQR: 712–1,842) U/L and 1,213 (IQR: 613–2,032) U/L in the HOPE group, and 1,943 (IQR: 1,294–5,214) U/L and 2,318 (IQR: 1,032–6,219) U/L in the SCS group (control). The levels were statistically significantly lower (p = 0.002 and p < 0.001, respectively). Median comprehensive complication index (CCI) in the main and control groups was 0 (IQR: 0–22.6) and 27.6 (IQR: 0–100) respectively. The differences were statistically significant (p = 0.001). Similarly, statistically significant differences were noted in terms of recipient time in the intensive care unit (ICU) and overall length of hospital stay (p = 0.042 and p = 0.028) – they were less in the HOPE group. Electron microscopy evaluation of the morphology of liver grafts revealed that hepatocytes sustained less injury during HOPE.Conclusion. Ex situ HOPE is a safe and effective way of preserving liver transplants. Its use in LTx from expanded criteria donors can lessen the severity of ischemia-reperfusion injury (IRI) in the organ and enable additional assessment of the suitability of an organ for transplantation.